Droplet Size and Distribution of Nebulized 3% Sodium Chloride, Albuterol, and Epoprostenol by Phase Doppler Particle Analyzer - Kelly McDermott, BS, RRT-ACCS; Jason G. Oakley, PhD (Elsevier, 2021)
ABSTRACT: Background: Aerosolized drug therapy administered to mechanically ventilated patients is a standard part of pulmonary critical care medicine. Aerosol particle size and distribution are important factors in the optimal delivery of aerosolized drugs to ventilated patients. Objective: The objective of this study was to characterize aerosol droplet size and distribution with laser diffraction for nebulized 3% sodium chloride, albuterol, and epoprostenol sodium (containing glycine) delivered via Aeroneb Solo Mesh Nebulizers (Aerogen, Mountain View, California). Methods: A series of functional flow tests were run on each of 8 Solo mesh nebulizers before the study to verify accuracy of flow rates in milliliters per minute. Aerosolized droplets exiting the nebulizer heads were then measured using a phase Doppler particle analyzer. Data collected during delivery of 3% sodium chloride, albuterol, and epoprostenol sodium included aerosol droplet size distribution, mass median aerodynamic diameter (MMAD), and geometric standard deviation. For each Solo nebulizer, droplet size measurements were taken 2 cm away from the nebulizer head and 2 cm away from the wye of a heated, humidified adult ventilator circuit. For measurements taken at the wye, 4 distinct, continuous flow rates (2, 10, 20, and 40 L/min) were generated by an air pump to simulate inspiratory flows delivered with mechanical ventilation. The expiratory limb was capped, and the nebulizer head was inserted into the breathing circuit upstream of the humidifier. Results: Each Solo nebulizer met Aerogen's recommended minimum flow rate of 0.2 mL/min, ranging from 0.23 to 0.31 mL/min. The MMAD of the 3 tested aerosols was several times smaller when measured at the wye outlet of the heated/humidified breathing circuit (0.82-2.73 µm) compared with droplets measured directly at the nebulizer outlet (MMAD, 4.6-7.3 µm). There was also significant variability across Solo heads with some ventilator flow rates. The mean MMAD at the wye for the 3% sodium chloride solution, albuterol, and epoprostenol test solutions was 1.62 µm, 1.09 µm, and 1.18 µm, respectively. The mean MMAD at the nebulizer for the 3% sodium chloride solution, albuterol, and epoprostenol test solutions was 5.37 µm, 5.73 µm, and 6.73 µm, respectively. Conclusions: Results from this study suggest that particle size of aerosolized drugs administered via a commonly used setup for delivery of in-line aerosols to mechanically ventilated patients may be several times smaller than expected and may result in less drug being delivered to the patient than previously realized.(Curr Ther Res Clin Exp. 2021; 82:XXX-XXX)© 2021 Elsevier HS Journals, Inc.